PERENCANAAN DAN PENYUSUNAN MUATAN PADA KAPAL LANDING CRAFT TANK (LCT) - Lis Lesmini; Amalia Anggraini; Muhammad Rifni (Jurnal Logistik Indonesia, 2019)
The purpose of this study was to determine the effect of load preparation planning on the effectiveness of load time, determine the effect of heavy load loading implementation on load time effectiveness and to determine the effect of load preparation planning and heavy load loading implementation on load time effectiveness. In this study found several problems that occur in the field including damage to mobile cranes, the occurrence of broken stowage and limitations of the dock which results in delays in the loading process. The population of this research respondents were 115 employees tested using Slovin theory, the minimum results obtained were 53 respondents and were sampled in this study. Validity test obtained by r table (n-2) = 53 respondents with a 5% error level that is equal to 0.270. Based on the test, it is said that all the items in each research variable are valid. The results of the Cronbach's Alpha reliability test of the three variables used in this study is greater than 0.60, it is concluded that the statements of each of these research variables are real. To test the variables as a whole where the variables X1 and X2 have an effect on Y variables simultaneously, the results of Fcount analysis are 28.664 and for Ftable values are 3.18. The value of Fcount> Ftable proves that Ho is rejected and Ha is accepted. Based on the analysis by linear regression, that the multiple correlation obtained by R for 0.731 or 73.1% means that the influence of X1 and X2 together on Y is positive and significant from the simultaneous test (F test) and the results of multiple correlation analysis, it can be concluded that variable X1 against Y with Correlation coefficient is 0.305 or 30.5% and X2 against Y with a correlation coefficient of 0.681 or 68.1%.